Working, living and dying in COVID times: perspectives from frontline adult social care workers in the UK. Issue 3 (5th August 2021) - Briggs, Daniel; Telford, Luke; Lloyd, Anthony; Ellis, Anthony
Abstract : Purpose: This paper aims to explore 15 UK adult social care workers' experiences during the COVID-19 pandemic. Design/methodology/approach: This paper's 15 open-ended interviews with adult social care workers are complemented by digital ethnography in COVID-19 social media forums. This data set is taken from a global mixed-methods study, involving over 2, 000 participants from 59 different countries. Findings: Workers reported a lack of planning, guidance and basic provisions including personal protective equipment. Work intensification brought stress, workload pressure and mental health problems. Family difficulties and challenges of living through the pandemic, often related to government restrictions, intensified these working conditions with precarious living arrangements. The workers also relayed a myriad of challenges for their residents in which, the circumstances appear to have exacerbated dementia and general health problems including dehydration, delirium and loneliness. Whilst COVID-19 was seen as partially responsible for resident deaths, the sudden disruptions to daily life and prohibitions on family visits were identified as additional contributing factors in rapid and sudden decline. Research limitations/implications: Whilst the paper's sample cohort is small, given the significance of COVID-19 at this present time the findings shed important light on the care home experience as well as act as a baseline for future study. Social implications: Care homes bore the brunt of illness and death during the first and second COVID-19 waves in the UK, and many of the problems identified here have still yet to be actioned by the government. As people approach the summer months, an urgent review is required of what happened in care homes and this paper could act as some part of that evidence gathering. Originality/value: This paper offers revealing insights from frontline care home workers and thus provides an empirical snapshot during this unique phase in recent history. It also builds upon the preliminary/emerging qualitative research evidence on how the COVID-19 pandemic impacted care homes, care workers and the residents.